The Visigoths in Gaul and Iberia (Update) : A Supplemental Bibliography, 2013-2015 - Ferreiro, Alberto (The Medieval and Early Modern Iberian World Ser, 2017)
Intro -- Contents -- Introduction -- Acknowledgements -- Periodical Abbreviations -- Reference -- (A) Bibliographies -- (B) Historiography -- (C) Personalia -- General Studies -- Hispania -- Invasions -- (A) Germanic -- (B) Muslim -- Social - Political - Economic -- Civil Law -- Literary Culture -- (A) Chronicles - Literature -- (B) Linguistics -- (C) Paleography -- Ecclesiastical -- (A) General Studies -- (B) Canon Law - Pseudo-Isidorus -- (C) Councils -- (D) Heresy -- (E) Monasticism -- (F) Organization -- Liturgy -- (A) Mariology -- (B) Music -- Patristics -- Apringius Pacensis -- Avitus Bracarensis -- Bachiarius -- Braulionis Caesaraugustanus -- Egeria in Gallecia Mon -- Eugenius Toletanus I, II, III -- Fructuosus Bracarensis -- Gregorius Illiberitanus -- Hagiographica -- Ildefonsus Toletanus -- Iohannes Biclarensis -- Iulianus Toletanus -- Leander Hispalensis -- Licinianus Cartaginensis -- Pacianus Barcinonensis -- Potamius Olisiponensis -- Prudentius -- Sisebutus Rex -- Taio Caesaraugustanus -- Valerius Bergidensis -- Miscellanea Patristica -- Isidorus Hispalensis -- Archaeology -- (A) General Studies -- (B) Urban and Rural Space -- (C) Architecture -- (D) Art -- (E) Epigraphy -- (F) Minor Arts -- (G) Numismatics -- (H) Funeraria -- Sueves -- (A) Social - Political - Economic -- (B) Archaeology -- (C) Ecclesiastical -- (D) Linguistics -- (E) Liturgy -- (F) Hydatius (Idacius) Aquae Flaviae ep. -- (G) Martinus Bracarensis -- (H) Orosius Paulus -- (I) Priscillianus Abulensis -- Toulouse -- (A) Archaeology -- (B) Ecclesiastical -- (C) Social - Political - Economic -- (D) Caesarius Arelatensis -- (E) Sidonius Apollinaris -- Other Peoples -- (A) Alans -- (B) Basques-Bagaudae -- (C) Byzantines -- (D) Jews -- (E) Vandals -- Collected Essays and Studia Honoraria -- (A) Collected Essays -- (B) Studia Honoraria -- Congresses - Symposia - Colloquia.